2016
DOI: 10.1039/c6tc01689h
|View full text |Cite
|
Sign up to set email alerts
|

A pyridine based meta-linking deep-blue emitter with high conjugation extent and electroluminescence efficiencies

Abstract: We designed and synthesized a bipolar deep-blue emitter 2,6-bis(4-(1-(4-(tert-butyl)phenyl)-1H-phenanthro[9,10-d]imidazol-2-yl)phenyl)pyridine (26BTPIPy) based on a meta-linking D-π-A-π-D stucture. Comparing to its para-linking analogue (25BTPIPy), the meta-linking in 26BTPIPy effectively shortens molecular conjugated length and restricts intramolecular charge transfer. Interestingly, unlike most other meta-linking emitters, a high fluorescent yield can be maintained in 26BTPIPy. This may be attributed to a re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 39 publications
0
19
0
Order By: Relevance
“…When N1 and C2 positions of PI are modified with a benzene ring, one of the most common and typical derivatives, namely 1,2‐diphenylphenanthroimidazole (PPI, Scheme 1) is obtained [25, 26] . PPI is a nitrogen‐containing heterocyclic conjugate group with a rigid planar conjugated structure having excellent properties, such as high fluorescence quantum yield and wide light absorption, which make it very attractive for employment as a building block for the preparation of blue emitters [27–30] . PPI can effectively reduce the energy loss of nonradiative transition and exhibits good thermal stability [31] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…When N1 and C2 positions of PI are modified with a benzene ring, one of the most common and typical derivatives, namely 1,2‐diphenylphenanthroimidazole (PPI, Scheme 1) is obtained [25, 26] . PPI is a nitrogen‐containing heterocyclic conjugate group with a rigid planar conjugated structure having excellent properties, such as high fluorescence quantum yield and wide light absorption, which make it very attractive for employment as a building block for the preparation of blue emitters [27–30] . PPI can effectively reduce the energy loss of nonradiative transition and exhibits good thermal stability [31] .…”
Section: Introductionmentioning
confidence: 99%
“…[25,26] PPI is an itrogen-containing heterocyclic conjugate group with ar igid planar conjugated structure having excellent properties, such as high fluorescenceq uantum yield and wide light absorption, whichm ake it very attractive for employment as a buildingb lock for the preparation of blue emitters. [27][28][29][30] PPI can effectively reducet he energy loss of nonradiative transition and exhibits good thermals tability. [31] Twod istinct nitrogen atoms in the imidazole ring make PPIb ipolar in nature, and thus PPI can not only be used as an electrona cceptor when combined with as trong electron-donor group, but also has the abilityt od onate electrons when coupled with an electron-deficientg roup or aweake lectron-donor group.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, along with introduction of the bulky SAF group, twist angle of the two central phenyl rings for SAF‐BPI have not changed with the angle of 35° compared with that for TPA‐BPI . Such moderate twist angle does not completely interrupt molecular conjugation and maintains high quantum yield . The optimized molecular geometries of SAF‐BPI and its derivative without tert‐butyl group ( SAF‐PPI ) were depicted in ESI Figure S5.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly,a long with introduction of the bulky SAF group, twist angle of the two central phenylr ings for SAF-BPI have not changed with the angle of 358 compared with that for TPA-BPI.S uch moderate twist angle does not completely interrupt molecular conjugation and maintains high quantum yield. [20] The optimized molecular geometries of SAF-BPI and its derivative without tertbutyl group (SAF-PPI)w ere depicted in ESI Figure S5. The tbuylated pheny ring/phenyl ring was highly twisted about the phenanthroimidazole plane with dihedral angles of 818 and 748 for SAF-BPI and SAF-PPI,r espectively.T he introductiono f tert-butyl group on phenanthroimidazole (BPI) unit could enhance the molecular distortion degree and help suppress the formation of aggregationo rp-p stacking in the solid state.…”
Section: Theoretical Calculationmentioning
confidence: 99%
“…[29][30][31][32][33][34][35][36] More importantly, linking topologies in molecular designing is an effective method to finetune electro-optical properties of materials. [37][38][39][40][41] For example, Sun et al systemically studied the impact of linking topology of carbazole-based arm on basic properties, found that HTMs based on carbazole-based arm with 2,7-substitution display higher hole mobility and conductivity than that of HTMs with 3,6-substitution. 41 While linking topology of core and arm are vital to determine properties of HTMs via developing continuous π-conjugation between core and arm, and tuning dihedral angles of small molecules, trivial attention has been made to the linking topology effect of core and arm.…”
Section: Independently Reportedmentioning
confidence: 99%